The legacy of the Monroe doctrine : a reference guide to U.S. involvement in Latin America and the Caribbean - Dent, David W. (Greenwood Press, 1999)
ntroduction -- Argentina -- Bolivia -- Brazil -- Chile -- Colombia -- Costa Rica -- Cuba -- Dominican Republic -- Ecuador -- El Salvador -- Grenada -- Guatemala -- Guyana -- Haiti -- Honduras -- Jamaica -- Mexico -- Nicaragua -- Panama -- Paraguay -- Peru -- Trinidad and Tobago -- Uruguay --Venezuela.